Partial Hydrolysis of Granular Potato Starch Using α‐Amylase – Effect on Physicochemical, Molecular, and Functional Properties. (20th November 2018) - Asiri, Saeed A.; Ulbrich, Marco; Flöter, Eckhard
Abstract : Potato starch (PS) is enzymatically modified using α‐amylase and comprehensively characterized. Modified PS is prepared by adding different amounts of α‐amylase (0.04, 0.08, 0.16, and 0.33 mL of an enzyme solution (LpHera, Novozymes A/S) to 400 g of a 40% w/v aqueous starch suspension and reacting for 15 min at 40 °C. Morphological characteristics (SEM), pasting (viscosity profile, thermal behavior‐DSC) and molecular properties (SEC‐MALS‐DRI), carbohydrates solubility, hot paste shear viscosity, and gel strength are analyzed. The morphological characteristics are significantly affected by the α‐amylase. The surface of the granules shows small cracks and holes. In regard to the characteristic pasting parameters, there are significantly decreased values after hydrolysis. However, the DSC gelatinization properties are slightly impacted by the modification. The solubility of the starch polymers is increased by the increase of both the enzyme dosage and the disintegration temperature applied (95 and 145 °C). Moreover, the molecular composition of the solubilized starch is impacted, too. The investigation of molecular dispersed solutions demonstrates the strong degradation of both amylose (AM) and amylopectin (AP). An increasing enzyme concentration led to a systematically decreased M w in the samples. The degradation within the amorphous areas is presumed to be faster, similar to acid hydrolysis in native granular starch. However, gelation properties of the enzymatically modified starches are not perceptible. The gradual depolymerization effected the reduction of the hot paste viscosity accordingly. Abstract : Potato starch (PS) is enzymatically modified using different amounts of α‐amylase (LpHera, Novozymes A/S) and comprehensively characterized. SEC‐MALS‐DRI experiments reveal a systematically changed molecular composition due to enzymatic degradation enhancing, e.g., the solubility. However, a distinct gelation behavior of the modified starches is not proved, most likely because of the extensive degradation of the amylose fraction.